(untitled) (Sains Humanika, 2010)
This study examined the relationships between quality of work life and work commitment, work stress and work satisfaction. This study also investigated the differences in work life quality, work commitment, work stress and work satisfaction based on demographic variables and the relationships amongst the variables. Questionnaire data was collected from a cross–sectional survey administered to 110 permanent teachers at a government secondary school in Kuching, Sarawak, Malaysia. Findings in this study showed that the respondents only had moderate work life quality. There were also moderate relationships between work life quality and work commitment, stress, and satisfaction but there were no differences in the quality of work life based on demographic variables. However there were differences in work commitment based on gender. This research also revealed that there were also no differences in work stress and satisfaction based on the same demographic variables. Similarly, the findings suggested that work commitment, work stress and satisfaction were not significantly correlated. Work life quality of teachers could still be improved to ensure that students gain maximum benefits from teaching and learning practices in the classrooms.